Struggle for New Media of Peace and Tolerance: A Close Look To the Usage of Internet in Defining and Building Young Muslim Community in Indonesia - Imam Malik Ridwan (Graduate Program of Pontianak Institute of Islamic Studies, 2015)
As for religion, internet has become a very important aspect in people’s everyday live, especially for those who seek information and further understanding about religion; internet is a way in and out to do so. While in one side internet has been a great help in providing sources and opportunity to learn religion in a new way, it also has a negative potential for the growing numbers of radicalism and religious extremism. Various researches and studies have bought up large data showing that these negative effects of internet bring bad influences to religious believers. Nevertheless, the ability of internet in providing and spreading information are also a way out in bringing back religion to its ideal path, that is to evoke peace and welfare among people. Internet is then used as a field for dakwah (proselytizing) to spread more peaceful as well as relevant information on religion and its related topics. Online dakwah is therefore meant to initiate peace and non-violent ways in understanding and practicing religion in real life. Focused targets for the dakwah are youth as the most active users of internet, as well as government to initiate and implement such policies to keep internet clean from violence and extremism.